Digital cost-control systems in international project activities and investment decision-making - Bikulov, Damir; Veritova, Olga; Oliinyk, Oleksandr; Sukhareva, Kateryna; Makazan, Yevheniia (Здобутки економіки: перспективи та інновації, 2025)
The purpose of the article is to deepen approaches to cost management and investment decision making in international projects through the development of an integrated digital model capable of overcoming the time and information gap between the emergence of financial deviations and managerial response by combining data, predictive risk analytics, and formalized managerial imperatives. Methods: The study applies systemic and structural functional analysis, comparative analysis of contemporary standards and digital cost management tools, as well as methods of predictive analytics and risk oriented modeling, which formed the basis for the development of the author’s framework concept «Cyber Physical Investment Governance» (CPIG) using vector cost decomposition and the «Multidimensional Adaptive Investment Control» algorithm (MAIC). Results:The concept of «Cyber Physical Investment Governance» (CPIG) has been developed, which implements an end to end cyber physical architecture for managing the investment cycle through sensory, cognitive, protocol, and execution layers. Five cost vectors are defined as the basis for causal interpretation of deviations, and a system of six investment imperatives is formed, strictly linked to forecasted risk levels and the phases of the international project life cycle. Conclusion: The proposed model ensures a transition to more effective, proactive, evidence based, and partially automated investment decision making, expanding theoretical perspectives on digital investment management and creating practical prerequisites for improving the validity, speed, and resilience of managerial decisions under conditions of high uncertainty in the international environment. The proposed concept also makes it possible to formalize the cause and effect relationship between risk, costs, and managerial action in real time, creating a foundation for scaling the CPIG framework in complex multi project and transnational investment portfolios.